(untitled) (Journal of Social Sciences Review, 2023)
With a rapid awareness about the role of Emotional Intelligence (EI) in academic achievement these days, the present paper attempts to investigate whether the Emotional Intelligence of ESL learners can be enhanced through EI-based language instruction so that learners can show good language performance. The research sample consisted of 100 ESL learners with mixed levels of learning achievement (or IQ) enrolled in the BS program at the department of English, The Islamia University of Bahawalpur. A questionnaire (consisting of 71 items) based on Petrides’ (2009) Trait Emotional Intelligence Questionnaire-Short Form and Austin et al.’s (2004) modified version of Schutte et al.’s (1998) and a self-compiled EI-based course were used as research instruments. Following the objectives of the study, a quantitative-cum-experimental research design was adopted to intervene in 100 ESL learners’ EI skills by giving them a course on explicit EI-based Language Instruction and measuring their EI skills before and after the intervention with the help of the aforementioned questionnaire. The findings revealed that after taking EI-induced language instruction, there was a significant increase in the EI skills of all participants, irrespective of the level of their learning achievement. However, students with a higher level of learning achievement benefit more from EI instruction as compared to the ones with lower learning achievement.